Piloting the use of accelerometry devices to capture energy expenditure in agricultural and rural livelihoods: Protocols and findings from northern Ghana. (2017) - Zanello, Giacomo; Srinivasan, C.S.; Nkegbe, Paul
Abstract: In this study we report on the protocols adopted and the findings from a pilot study in northern Ghana involving 40 respondents wearing accelerometry devices for a week. We show how integrating energy expenditure data from wearable accelerometry devices with data on activity and time-use can provide a window into agricultural and rural livelihoods in developing country contexts that has not been previously available for empirical research. Our findings confirm some of the stylised facts of agricultural and rural livelihoods, but the study also provides several new insights that come from the triangulation of energy expenditure, time use, and activity data. We report findings and explore the potential applications of using accelerometry devices for a better understanding of agriculture-nutrition linkages in developing countries.